Love-at-arms - Sabatini, Rafael, 1875-1950 (Salt Lake City, UT : Project Gutenberg, 2002)
"Love-at-arms: Being a narrative excerpted from the chronicles of Urbino" by Raphael Sabatini is a historical novel set during the late 15th to early 16th century, a tumultuous time in Italian history marked by political intrigue and power struggles among the noble houses. The story revolves around Francesco del Falco, the Count of Aquila, who becomes embroiled in conspiracy and treachery as he is approached by nobles seeking to dethrone Gian Maria Sforza, the self-indulgent Duke of Babbiano. The narrative promises themes of loyalty, ambition, and the conflicts between personal integrity and political duty. At the start of the novel, we are introduced to a clandestine meeting held by several discontented nobles in a hovel, where they discuss their grievances against Duke Gian Maria. As tensions rise with fears of betrayal by a lurking spy, the ancient noble Fabrizio da Lodi proposes a bold plan to replace the Duke with the Count of Aquila, emphasizing his courage and reputation. The Count expresses reluctance due to his ties to the Duke but ultimately agrees to aid them in seeking reforms. The opening chapters set the stage for an intense power struggle within the backdrop of romantic entanglements, specifically highlighting the fate of Valentina della Rovere, the Duke's betrothed, and her interactions with Aquila, amid the prevailing atmosphere of conspiratorial danger that surrounds them. (This is an automatically generated summary.)
Release date is 2002-11-01
John Stuart Middleton, and David Widger
Keywords: Italy -- History -- 1492-1559 -- Fiction; Arranged marriage -- Fiction; Borgia, Cesare, 1476?-1507 -- Fiction; Urbino (Italy) -- Fiction